Microshear bond strength of conventional and self-adhesive resin cements to feldsphatic ceramic - Estéfani Maminis Soares Couto; Bruna de Oliveira Reis; Thaís Yumi Umeda Suzuki; Wirley Gonçalves Assunção; André Luiz Fraga Briso; Paulo Henrique dos Santos (Universidade Estadual de Campinas, 2018)
Aim: The aim of this study was to verify the microshear bond strength of conventional and self-adhesive resin cements to feldsphatic ceramic. Methods: Twenty discs of Starlight ceramic (Degudent) were made (15mm x 2mm). The bonding procedure was accomplished by insertion of resin cements into tubes of 0.7mm internal diameter in contact with the ceramic. The resin cements used were: RelyX ARC (3M Espe), Panavia F (Kuraray), RelyX Unicem (3M Espe) and seT (SDI). Total of six tubes of each material on each ceramic disc. The specimens were tested for microshear in a universal testing machine, 24hours and 6months after bonding procedure. Values of microshear bonding strength (MPa) were subjected to ANOVA and Fisher PLSD test (p<0.05). Results: For 24hours analysis, RelyX ARC showed the highest microshear bonding strength without statistical difference to RelyX Unicem and seT. Panavia F showed the lowest values of microshear bonding strength in both periods. In the analysis after 6months there was a significant increase in the microshear bonding strength values for all cements compared to 24hours. Only for RelyX ARC, the increase was not statistically significant. Conclusion: In conclusion, the bond strength depends mainly on the type of resin cement used, and the self-adhesive cements behave similarly to conventional resin cement.